2007
DOI: 10.1007/s00468-006-0113-z
|View full text |Cite
|
Sign up to set email alerts
|

The holoparasitic endophyte Bdallophyton americanum affects root water conductivity of the tree Bursera simaruba

Abstract: It has been reported that parasitic vascular plants (hemiparasites and holoparasites) may affect host fitness, but the effects produced by root endophyte holoparasitic species on its host have not been documented. Here the effect of the holoparasitic endophyte Bdallophyton americanum (R. Br.) Harms on the root conductivity of Bursera simaruba (L.) Sarg. was studied. Parasitized and non-parasitized root segments were sampled in the rainy and dry seasons in a dry coastal forest in central Veracruz, Mexico. Root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Br.) Harms affecting Bursera simaruba (L.) Sarg., where K s on parasitized roots during the dry season was 61% lower than in non-parasitized roots (García-Franco et al 2007). We cannot compare our results with epiphytic plants per se, because there is no literature about effects of damage by epiphytes on the vascular system of plants.…”
Section: Discussionmentioning
confidence: 69%
“…Br.) Harms affecting Bursera simaruba (L.) Sarg., where K s on parasitized roots during the dry season was 61% lower than in non-parasitized roots (García-Franco et al 2007). We cannot compare our results with epiphytic plants per se, because there is no literature about effects of damage by epiphytes on the vascular system of plants.…”
Section: Discussionmentioning
confidence: 69%
“…These findings are also in agreement with those found by Gomes and Fernandes (1994) who showed that the direct reduction in plant size due to parasitism of Pilostyles ulei (P. ingae) can influence M. maguirei architecture through reduction in apical dominance and consequent increased branching. Probably this also increases water loss through transpiration due to greater surface area as suggested in the case of Bdallophyton (García-Franco et al 2007). This form /size effect might be the ultimate expression of the action of the two limiting factors: water and sugar.…”
Section: Discussionmentioning
confidence: 93%
“…Blossoming and fruiting are some of the most important energy drains in the plant life cycle as has been demonstrated in classical papers (Murneek 1932;Wardlaw 1990). This drain occurs normally when the host blossoms, but parasitized plants, in addition to investing products of photosynthesis in its own growth, also lose them to the parasites (Press 1995;García-Franco et al 2007). Parasites, during reproduction, produce many flowers and fruits along the stems of the host, and these flowers may produce copious quantities of nectar and store sugar, starch and oil in fruits and seeds.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, substantial alterations to the host xylem micromorphology occur. In general, a proliferation of host vascular tissue made up of small vessels at high density occurs during endoparasite bud development (García‐Franco et al ., 2007; Amaral & Ceccantini, 2011; Teixeira‐Costa et al ., 2021). These observations suggest that while endoparasite infestation reduces host efficiency in sap‐conductivity, it may also optimize xylem ‘hydraulic safety’ in the longer term.…”
Section: Patterns Of Convergence In Life History Among Endoparasitic ...mentioning
confidence: 99%